Neurofuzzified Analysis on Torque Control of a Squirrel Cage Induction Machine - Osundina, Emmanuel; Peter Daffin Onwe; Eluebo Emmanuel Chuka; Awominure , Ajoke Alice; Tosin Tunde Oyetayo (Tinta Emas Publisher, 2024)
The direct torque controller (DTC) is an interesting control scheme for induction motor control. It is suitable for variable-frequency drives for torque and its consequent speed control, specifically for the calculation of the estimated Induction motor's magnetic flux and torque based on the motor's measured voltage and current. However, this scheme has a disadvantage in its implementation that makes it unsuitable for high torque applications, resulting in poor drive parameter variation, optimization, and dynamic responses when compared to field-oriented control (FOC). Fuzzy-based DTC is introduced to control. The high torque ripple nature of the direct torque-controlled induction motor improves drive performance to parameter variation, and improve transient response to step changes in torque during start-up. The neurofuzzy analysis on torque performance under load disturbance shows a transient response and a low step ripple effect. Thus, this improved scheme is recommended for a high inertia application. Such as flywheel presses and rock crushes.